Divergent response associates with the differential amplitudes of immunity against Magnaporthe oryzae by different blast resistance genes - Hassan, Beenish; Bhutto, Sadam Hussain; Yin, Xiao-Xiao; Yan, Xiu-Lian; Liao, Rong; Guo, Mao-Lin; Tang, Ya-Ping; Guo, Dai-Ming; Yang, Si-Jia; Gulzar, Faiza; Li, Yan; Zeng, Xian-Yin; et al. (Frontiers in Plant Science, 2025)
Rice blast disease, caused by Magnaporthe oryzae, poses the most devastating threat to global rice production. The products of most blast resistance (R) genes specifically recognize corresponding a virulence effectors from the pathogen, thereby mediating robust immune responses that are crucial for disease resistance. However, it is unclear why different R genes endow with differential amplitudes of immunity against M. oryzae. Here, we demonstrated that different blast R genes confer differential amplitudes of immunity against M. oryzae, presumably due to divergent reprogramming of transcriptional responses. We detected that three rice restorer lines exhibited differential amplitudes of immune responses, despite all lines displaying resistance to M. oryzae. Consistently, different accessions carrying different single R genes exhibited remarkable differentially expressed genes (DEGs) count, indicating different transcriptional re-programming that leads to different fitness cost. Comparative analysis revealed varying degrees of overlap among DEGs across different accessions. By integrating RNA-seq and RT-qPCR data, we recommended some marker genes that distinguish the differential amplitude of immunity against M. oryzae mediated by different blast R genes. Thus, our study provides valuable insights into the specific and overlapping roles of R gene-mediated immunity. We also propose marker genes that can be used to effectively evaluate the amplitude of immune responses to M. oryzae, thereby facilitating the assessment of R genes with relatively lower amplitude of immunity in order to minimize fitness cost.